1994
DOI: 10.1103/physrevlett.72.352
|View full text |Cite
|
Sign up to set email alerts
|

Low-order modes as diagnostics of spheroidal non-neutral plasmas

Abstract: In many experiments on single-component plasmas, including antimatter plasmas, the standard diagnostic techniques used to measure the density and temperature are not appropriate. We present a new method for determining the size, shape, average density, and temperature of a singlecomponent plasma confined in a Penning trap from measurements of the plasma mode frequencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
78
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(81 citation statements)
references
References 21 publications
3
78
0
Order By: Relevance
“…Simultaneously, we monitor the quadrupole vibrational mode of the plasma by applying an oscillating potential at 26.5 MHz to an electrode adjacent to the plasma and measuring the plasma response on another. The frequency of this mode shifts approximately linearly with changes in temperature 15 . When the microwave frequency matches the cyclotron frequency, the heating of the plasma and the quadrupole frequency shift will be maximized.…”
mentioning
confidence: 91%
“…Simultaneously, we monitor the quadrupole vibrational mode of the plasma by applying an oscillating potential at 26.5 MHz to an electrode adjacent to the plasma and measuring the plasma response on another. The frequency of this mode shifts approximately linearly with changes in temperature 15 . When the microwave frequency matches the cyclotron frequency, the heating of the plasma and the quadrupole frequency shift will be maximized.…”
mentioning
confidence: 91%
“…The positron temperature is monitored using the plasma mode analysis technique of ref. 12. The two mechanisms of antihydrogen formation expected to be important in ATHENA, radiative recombination and three-body recombination 16 , should be effectively suppressed at the hot mixing temperature, although the positrons and antiprotons still interact.…”
mentioning
confidence: 99%
“…In ATHENA, the spheroidal cloud of positrons can be characterized by exciting and detecting axial plasma oscillations, as demonstrated by ref. 12. Typical conditions are: 7 £ 10 7 stored positrons, a radius of 2-2.5 mm, a length of 32 mm, and a maximum density of 2.5 £ 10 8 cm 23 .…”
mentioning
confidence: 99%
“…A cold fluid theory [7] relating the frequencies of the low-order plasma modes to the density and the aspect ratio of spheroidal plasmas was confirmed experimentally for laser cooled ion plasmas [8,9] and successfully applied to cold electron plasmas [10]. Work on finite temperature electron plasmas demonstrated that mode detection could be used as a diagnostic of density and aspect ratio and that for a plasma of known density and aspect ratio the frequency of the quadrupole mode is dependent on the plasma temperature [11,12].Here we describe an extension to the above work which provides a non-destructive diagnostic based on measurements of the first two axial modes of a finite temperature positron plasma. The diagnostic has no discernable effect on the normal evolution of the plasma, so it can be used…”
mentioning
confidence: 94%
“…Because of the importance of temperature in antihydrogen production, we have also investigated whether this diagnostic system can be used to detect changes in the plasma temperature. Previous authors have demonstrated, with work on similar electron plasmas [11,12], that temperature changes manifest themselves in frequency shifts of the quadrupole mode. In particular they find…”
mentioning
confidence: 99%